Antithrombotic Treatment of Splanchnic Vein Thrombosis: Results of an International Registry - Ageno, Walter; Riva, Nicoletta; Schulman, Sam; Bang, Soo Mee; Sartori, Maria Teresa; Grandone, Elvira; Beyer-Westendorf, Jan; Barillari, Giovanni; Di Minno, Matteo Nicola Dario; Dentali, Francesco; null (Seminars in Thrombosis and Hemostasis, 2014)
Treatment of splanchnic vein thrombosis (SVT) is a clinical challenge due to heterogeneity of clinical presentations, increased bleeding risk, and lack of evidences from clinical trials. We performed an international registry to describe current treatment strategies and factors associated with therapeutic decisions in a large prospective cohort of unselected SVT patients. A total of 613 patients were enrolled (mean age 53.1 years, standard deviation ± 14.8); 62.6% males; the majority (468 patients) had portal vein thrombosis. Most common risk factors included cirrhosis (27.8%), solid cancer (22.3%), and intra-abdominal inflammation/infection (11.7%); in 27.4% of patients, SVT was idiopathic. During the acute phase, 470 (76.7%) patients received anticoagulant drugs, 136 patients (22.2%) remained untreated. Incidental diagnosis, single vein thrombosis, gastrointestinal bleeding, thrombocytopenia, cancer, and cirrhosis were significantly associated with no anticoagulant treatment. Decision to start patients on vitamin K antagonists after an initial course of parenteral anticoagulation was significantly associated with younger age, symptomatic onset, multiple veins involvement, and unprovoked thrombosis. Although a nonnegligible proportion of SVT patients did not receive anticoagulant treatment, the majority received the same therapies recommended for patients with usual sites thrombosis, with some differences driven by the site of thrombosis and the pathogenesis of the disease.
Keywords: splanchnic vein thrombosis; heparin; vitamin K antagonist